Effect of chemical insecticide application for control of the whitetly Aleurotrachelus socialis (Homoptera: Aleyrodidae) in cassava Manihot esculenta Crantz - HOLGUÍN-A., CLAUDIA MARÍA; BELLOTII, ANTHONY C. (Revista Colombiana de Entomología, 2004)
In recent years the whitetly Aleurotrachelus socia/is Bondar has been the most important pest affecting the cassava  crop in Colombia. In order to search for different alternatives in an integrated management program, three experlrnents were conducted under field conditions in Jamundi (Valle del Cauca) in a complete randomized block design, with the cassava variety Reina. In the first trial the foliar application of different insecticides was evaluated. The  treatments corresponded to imidacloprid 1, buprofezin, carbosulfan, tiametoxan, diafentiuron, piriproxifen and  imidacloprid 2. In the other two experiments we sought to delay appearance of the pest by evaluating different doses, forms an application periods of imidacloprid: drench of the seed at planting and emergence of the first leaf. and stake immersion, reinforced with foliar applications. In ali experiments egg, nymph and adult populations were evaluated based on a population scale  ofl to 6. The  foliar application with tiametoxan, imidacloprid  I  and  2 presented the lowest population values for adults. eggs and nymphs compared to the control. When imidacloprid was used al planting and immersion or seed drenching, the crop was protected between 45 and 60 days. Al the economic level, for farmers with large planting areas the benefits are greatest by using only foliar applications. For small-scale farmers chemical control is only beneficia! with one product in foliar form. When used  from planting on. the small-scale farmer gained no benefits from any of the treatments.